2003
DOI: 10.1364/oe.11.002597
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of higher closed�??loop bandwidths in ocular adaptive optics

Abstract: We present an ocular adaptive optics system with a wavefront sampling rate of 240 Hz and maximum recorded closed-loop bandwidth close to 25 Hz, but with typical performances around 10 Hz. The measured bandwidth depended on the specific system configuration and the particular subject tested. An analysis of the system performance as a function of achieved bandwidth showed consistently higher Strehl ratios for higher closed-loop bandwidths. This may be attributed to a combination of limitations on the available t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
53
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 10 publications
4
53
0
Order By: Relevance
“…It should be noted that frequencies just below the Nyquist frequency are boosted by aliasing effects due to frequencies just above this frequency. Furthermore, a similarity can be noted between the power spectrum obtained for tear film variations in this work and those obtained elsewhere for overall dynamic eye aberrations [5,6]. Frequency (Hz) Power (normalised coordinates) Fig.…”
Section: Frequency Domain Analysissupporting
confidence: 83%
See 1 more Smart Citation
“…It should be noted that frequencies just below the Nyquist frequency are boosted by aliasing effects due to frequencies just above this frequency. Furthermore, a similarity can be noted between the power spectrum obtained for tear film variations in this work and those obtained elsewhere for overall dynamic eye aberrations [5,6]. Frequency (Hz) Power (normalised coordinates) Fig.…”
Section: Frequency Domain Analysissupporting
confidence: 83%
“…8, shows that there are measurable contributions to the tear film aberrations at least up to 11Hz, which is the highest frequency measurable in this work. The presence of these higher frequency components might corroborate the argument for using higher closed loop bandwidths in adaptive optics systems [5], though the improvement in optical quality this would bring might be small, especially in relation to the higher technical challenges required for running at higher bandwidths. It should be noted that frequencies just below the Nyquist frequency are boosted by aliasing effects due to frequencies just above this frequency.…”
Section: Frequency Domain Analysismentioning
confidence: 73%
“…They calculated the power spectrum of these temporal series and found that it presented a very characteristic behaviour for all eyes studied: when plotted in log-log scale it appeared as a straight line with a negative slope of -1.5, up to 12Hz. A later study by Diaz-Santana et al observed similar behavior down to 30Hz [5], while another work by Nirmaier et al found similar behavior down to 70Hz [6]. The mechanisms behind this behaviour have not yet been understood.…”
Section: Introductionmentioning
confidence: 89%
“…This methodology has been used extensively to measure static aberrations. However, the dynamics of these aberrations beyond defocus and astigmatism have not been as extensively studied [3,4,5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…They subsequently demonstrated that the dynamic AO indeed achieved improved correction for the ocular wave aberration over the static AO correction [2]. However, Diaz-Santana et al later found that the temporal frequency of the ocular wave aberration in the human eye could be up to 30 Hz [19], and Nirmaier et al even reported that the temporal frequency of the ocular wave aberration could be as high as 70 Hz [20]. Through a systematic study of the temporal dynamics of ocular wave aberrations monocularly and binocularly in the relaxed and accommodated state, Mira-Agudelo et al confirmed the high frequency fluctuation (up to 30 Hz) [21].…”
Section: Introductionmentioning
confidence: 99%